Hybrid of Europium‐Doped Layered Yttrium Hydroxide and Organic Sensitizer – Effect of Solvent on Structure and Luminescence Behavior. Issue 1 (13th November 2012) - Sun, Yahong; Chu, Nankai; Gu, Qingyang; Pan, Guohua; Sun, Genban; Ma, Shulan; Yang, Xiaojing
Abstract: The organic sensitizer terephthalic acid and its anion terephthalate (TA) were introduced into the galleries of europium‐doped layered yttrium hydroxide (LYH:Eu). In contrast to using water as solvent, the use of formamide resulted in the introduction of more organic guests and markedly enhanced the Eu 3+ luminescence. Formamide prevented water from entering the system, leading to an excess of terephthalic acid molecules, and more efficient coordination of the TA guest with the Eu 3+ in the layers of the composite, all of which may have contributed to the enhanced Eu 3+ luminescence. Abstract : The organic sensitizer terephthalic acid and its anion terephthalate (TA) were introduced into the galleries in europium‐doped layered yttrium hydroxide (LYH:Eu). The use of different solvents led to the formation of various hybrid structures and brought about distinct Eu 3+ luminescence behavior.